The microRNA bantam regulates a developmental transition in epithelial cells that restricts sensory dendrite growth - Jiang, Nan; Soba, Peter; Parker, Edward; Kim, Charles C.; Parrish, Jay Z. (Development, 2014)
As animals grow, many early born structures grow by cell expansion rather than cell addition; thus growth of distinct structures must be coordinated to maintain proportionality. This phenomenon is particularly widespread in the nervous system, with dendrite arbors of many neurons expanding in concert with their substrate to sustain connectivity and maintain receptive field coverage as animals grow. After rapidly growing to establish body wall coverage, dendrites of Drosophila class IV dendrite arborization (C4da) neurons grow synchronously with their substrate, the body wall epithelium, providing a system to study how proportionality is maintained during animal growth. Here, we show that the microRNA bantam (ban) ensures coordinated growth of C4da dendrites and the epithelium through regulation of epithelial endoreplication, a modified cell cycle that entails genome amplification without cell division. In Drosophila larvae, epithelial endoreplication leads to progressive changes in dendrite-extracellular matrix (ECM) and dendrite-epithelium contacts, coupling dendrite/substrate expansion and restricting dendrite growth beyond established boundaries. Moreover, changes in epithelial expression of cell adhesion molecules, including the beta-integrin myospheroid (mys), accompany this developmental transition. Finally, endoreplication and the accompanying changes in epithelial mys expression are required to constrain late-stage dendrite growth and structural plasticity. Hence, modulating epithelium-ECM attachment probably influences substrate permissivity for dendrite growth and contributes to the dendrite-substrate coupling that ensures proportional expansion of the two cell types. © 2014. Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2021-11-16
Keywords: Dendrite; Drosophila; Endoreplication; Extracellular matrix; Growth control; Plasticity